Moderating role of marketing environment on the lead success factors of halal small and medium enterprises in Pahang / Putri Rozita Tahir - Tahir, Putri Rozita (2013)
The importance and the role played by entrepreneurship and entrepreneurs in the growth and development of the Malaysian economy cannot be denied. As businesses become more complex, the current dynamic business environment makes it necessary for organizations to employ effective plans of action and business strategies. Recognizing the importance of the contributions of Small and Medium Enterprises (SMEs), the government plays a crucial function in generating, developing and enabling conducive environment for SMEs to operate and succeed. Several studies that were conducted previously on SMEs emphasize primarily on observing and reporting the profile of the SMEs, the personal characteristics of the SME owners, problems and constraints faced by them, the factors that leads to performance and success of SMEs, and the assistance programmes provided by the government. However, there was no special attention given to SMEs that operate in the halal industry. Such investigations are exposed to several limitations and appear to be of little help to provide framework for better understanding of the SMEs that operate in the halal industry. Unlike general SMEs where there is no rigid and unique requirement to adhere to, halal SMEs face an environment in which their characteristics and operations are strictly controlled by guidelines set according to the Syariah law. As such, the environment in which the halal SMEs operate may pose opportunities and challenges that can either be conducive or not conducive for the success of halal SMEs. SME owners need to be educated and trained to face the unique requirements in the halal environment, and should also be able to assess their own personal characteristics in order to succeed in such environment. Therefore, in line with Malaysia’s effort to put the local SMEs in the global halal market, this study iii examines whether the halal marketing environment acts as a moderator to influence the effect of two lead success factors chosen, namely, the types of entrepreneurship education and training that the SME owners attended and the personal characteristics of the SME owners on the success of halal SMEs. Qualitative and quantitative approaches were used in the research design as the personal interview conducted enhanced the survey instruments used to examine the relationships. The SMEs registered with the Pahang State Development Corporation for the halal industry was chosen as the sample in this study because of their owners’ active participations and proactive efforts for their own development in the halal business. Results of correlation revealed that there is a strong relationship between the types of entrepreneurship education and training and the level of success for halal SMEs, and between the personal characteristics of the SME owners and the level of success of halal SMEs. The role of marketing environment as a moderator was tested using hierarchical multiple regression, and results showed that it does moderate the effect of the lead factors on the SMEs in this study. The research significantly provides a better understanding of why the halal SMEs should be studied as a separate entity from the general SMEs based on how the SME owners perceived the effect of the environment and how they would increase the level of success by implementing a realistic and practical approach to their businesses to suit the environment. The findings from this study also add to the information on the suitability of the types of entrepreneurship education and training that the SME owners attended and the personal characteristics of the SME owners and how they are moderated when such environment like the halal environment exist. By recognizing and understanding the uniqueness of the halal environment, government bodies and legislative bodies would be able to better prepare the SMEs to be successful in the global halal market.